COMPARATIVE OF PIEZOELECTRIC AND CONVENTIONAL OSTEOTOMY FOR LOWER THIRD MOLAR IMPACTION EXTRACTION WITH SUBMUCOSAL DEXAMETHASONE INJECTION - Senan, Sohaib Ezzi Dhaif Allah; Farhan, Abdullah HT; Shareef, Ala،a Ahmed M; Al-Shamahy, Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2024)
Background and aim: The most common procedure performed in the outpatient setting in maxillofacial surgery practices is the extraction of impacted third molars. This technique often requires incision, flap reflection, and bone removal, which causes tissue stress and involves large amounts of connective tissue and blood vessels in the third molar area. The aim of this study was to examine decompression surgery and the rotary technique alone and to evaluate the combined effect of decompression surgery and conventional osteotomy with submucosal dexamethasone injection on the sequelae after surgical extraction of impacted mandibular third molars. Methodology: With a sample of sixty individuals, a randomized controlled clinical trial was carried out. Four groups of fifteen participants each were created: Group 1 was for conventional rotatory therapy; Group 2 was for conventional rotatory therapy plus a 4 mg dose of dexamethasone following surgery; Group 3 was for piezosurgery; and Group 4 was for piezosurgery plus a 4 mg dose of dexamethasone following surgery. The surgical working time was determined in minutes, the maximum mouth opening was measured in millimeters at baseline and on the second, fifth, and seventh day using a Vernier Caliper, and the postoperative pain was quantified using a Visual Analog Scale (VAS) every day for the first week. Result: A study involving 36 women and 24 men aged 21-32 years performed a procedure involving impacted lower third molars, with a 100% success rate. All patients showed soft tissue healing without serious events or infection. Pain levels were greater in group 3 (3.7 degrees) and lower in group 2 (2.6 degrees). No significant differences were found in pain levels of dexamethasone injection among the four groups. Conclusion: The use of submucosal dexamethasone injection with conventional and electrosurgical osteotomy is beneficial for alleviating post operative complication after removal of impacted third molar surgery. Peer Review History: Received 11 July 2024; Reviewed 17 September 2024; Accepted 23 October; Available online 15 November 2024 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewers: Dr. Ahmad Abdelsattar El-Ebiary, Tanta University Hospitals, Tanta, Egypt, a.ebiary@med.tanta.edu.eg Dr. George Zhu, Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com